Effect of wearing medical protective masks on treadmill running performance in the postpandemic era: a randomised trial - I-Lin Wang; Yu Su; Shun Yao; Yu-Hong Jiang; Hao-Yu Li; Chien-Ying Lai (BMC, 2023)
Abstract Background In the postpandemic era, wearing protective masks in public places will still be an important means of blocking popular viruses in the future. The purpose of this study was to explore whether sports performance was affected by mask wearing and exercise duration during 15-min treadmill running at a speed of 75% maximal aerobic speed. Methods Thirty-six males were randomly divided into mask and nonmask groups. The kinematic and kinetic data were obtained at four time points (RN0-1 min, RN5-6 min, RN9-10 min, and RN14-15 min) during running. Two-way mixed ANOVA was applied to examine the effects between groups and times with Bonferroni post hoc comparison and independent samples t-test. Results The results showed that there was no difference between mask and nonmask group during running (p > 0.05). As running time increased, hip joint ROM, hip joint flexion/extension max, and ankle joint plantarflexion max angles increased; knee joint flexion min and ankle joint dorsiflexion max angles decreased; average peak vertical ground reaction forces (PVGRF) increased after 9 min-running (p < 0.05). Conclusions Wearing a medical protective mask does not affect the joint angle and touchdown PVGRF of lower extremities during treadmill running while affected by running time and changed after 9 min-treadmill running. Future studies will examine the effects of wearing masks during the pandemic on muscle activation and blood biochemical values during exercise. Trial registration No. ChiCTR2000040535 (date of registration on December 1, 2020). Prospectively registered in the Chinese Clinical Trial Registry.